(untitled) (Research, Society and Development, 2020)
Advances in the area of Chemistry directly affect the daily lives of each one. For society to understand how these advances relate to the community and their personal interests, we must use tools that facilitate interdisciplinarity between environmental issues and the teaching of chemistry. Undergraduate students in Chemistry and related fields need to use the knowledge acquired during their course in such a way that certain content contributes to their socio-scientific understanding. By debating issues related to the environment that involve Chemistry, we can create an environment conducive to the development of the Chemistry professional with an emphasis on relating green Chemistry to the current situation on the planet. This article aims to analyze, through a bibliographic review of Revista Química Nova, the articles that work with biodiesel in the teaching of Chemistry in the context of the classroom for undergraduate students. For this, a survey was carried out in Revista Química Nova in the Education section, from 2014 to 2019, looking for articles that work with biodiesel as a teaching tool for undergraduate students. Four articles were found with these requirements, in which the authors worked both on the production of biodiesel using diversified raw materials for practical classes in the discipline of Organic Chemistry, as well as scientific development in an oral way, debating or reflecting on biodiesel in a way that helps in the formation of the undergraduate student’s scientific communication, the methodology was carried out in the journal Química Nova na Escola, and data analysis was performed through qualitative document analysis.